Legislative secretariat support services to the Sangguniang Panlalawigan Members of Region I - Mariano, Ma. Anna Josephine G. (San Fernando City, La Union : [s.n.], 2014)
The study sought to assess the level of performance of the Legislative Secretariat in providing support services to the Sangguniang Panlalawigan of Ilocos Norte, Ilocos Sur, La Union and Pangasinan in performing their legislative tasks and responsibilities for the period 2010-2013 as basis for formulating a capability building program for the legislative secretariat for the said provinces in terms of their duties and functions; extent of involvement of the Sangguniang Panlalawigan secretariat in terms of the four legislative domains; the strengths and weaknesses of the Sangguniang Panlalawigan Secretariat; and the problems encountered by the legislative secretariat. This study conducted in the four provinces of Region 1, namely: Ilocos Norte, Ilocos Sur, La Union and Pangasinan. It made use of the descriptive method using a questionnaire as the main data gathering tool. There were two sets of respondents, namely: the Sangguniang Panlalawigan Members, and the Legislative Secretariat of the said provinces. The study found out that the SP Secretariat of the four provinces is very satisfactory in the performance of their duties and functions; moderately involved in the four legislative domains; there were problems encountered by the legislative secretariat with varying degree of seriousness in their performance of their functions as support group to the SPMs, thus paved for consideration in the Capacity Building Program. The Capacity Building Program's design included two phases based from the findings of the study.
Bibliography: pages 103-105.
CHED-La Union
Keywords: Legislative bodies